The outcomes of a frenulotomy on breastfeeding infants followed up for 3 months at Thammasat University Hospital - Wakhanrittee J. (2017)
© 2016, Springer-Verlag Berlin Heidelberg. Purpose: To study the effects of frenulotomy on nipple pain, latch and the success in exclusive breastfeeding (EBF) at 3-month follow-up. Methods: A prospective cross-sectional study of 328 mother–infant pairs with both tongue-tie and breastfeeding problems was performed. Nipple pain and latch were evaluated using numeric rating scale and LATCH score, respectively, and compared between pre and post-operatively at 24 h and 1 week. The success rate of EBF was assessed at 3 months after frenulotomy. Results: Nipple pain score were significantly decreased (median difference = 3 and 4, P  <  0.001) and LATCH score were significantly increased (mean difference = 1.92 and 2.13, P  <  0.001) at 24 h and 1 week post-operatively. At 3 months, a success rate of EBF was 66.67 %. Multivariable analysis clustering by maternal age of 18 years was performed. Factors that were significantly (P  <  0.05) associated with the success were: girls, age at surgery ≤24 h, higher number of children in family, low birth weight, tongue-tie severity, nipple grading, LATCH score ≥8 and nipple sensation at 1 week after surgery. Conclusion: Frenulotomy could significantly reduce nipple pain and increase LATCH score in tongue-tied infants with breastfeeding difficulty. Several factors are positively associated with the success of EBF. Tongue-tie severity, LATCH score and nipple sensation were the factors that can be modified by frenulotomy.